Tindak Tutur Ilokusi pada Podcast Deddy Corbuzier Eposide Jessica Wongso, Riset Ini Netflix Tidak Punya - Havizah, Sofia Nur; Muhajir, Muhajir (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This study aims to gain an understanding of the various forms and functions of illocutionary speech acts in Deddy Corbuzier's podcast which discusses Jessica Wongso's case data ice cold that is notowned by Netflix, recently became a public conversation about a film entitled Ice Cold. The type ofresearch used is the qualitative descriptive method. The data used in this study was in the form of speech transcripts consisting of sentences or paragraphs showing the location of illocutionary speech acts in Deddy Corbuzier's podcast on Youtube social media. The source of the research data is in the form of a video podcast Deddy Corbuzier episode of Jessica Wongso, this research Netflix does not have. In this study, data collection techniques used recording techniques and free listening methods. Based on the results of the study, various types of illocutionary speech acts were found according to Searle in Tarigan, the forms of illocutionary speech acts found were classified into five main categories, namely assertive, directive, declarative, commissive, and expressive.